Mental Health and Diabetes Mellitus: psycho-emotional changes during the period of social distance in the COVID-19 pandemic (Research, Society and Development, 2020)
Objective: To characterize the mental health state of individuals with diabetes mellitus and to identify determining factors for their imbalance, during the period of the COVID-19 pandemic. Methodology: It is a cross-sectional, quantitative exploratory study, developed between August and September of 2020. The 126 people covered in the study were submitted to a questionnaire answered virtually, based on Self-Report Questionnaire (SRQ-20), which addressed issues of the socio-demographic situation and psycho-emotional state during the period of social distance adopted in the COVID-19 pandemic. The results were analyzed by descriptive and inferential statistics.  Results: There were changes in psycho-emotional aspects due to the challenge of daily life and a change in routine during the pandemic. All of this evidence resulted in mental stress associated with frequent headaches. It was found that 50% of the elderly developed worthlessness feelings, considering the familiar dependence to accomplish basic routine activities. There was an impact of decreased income on the psycho-emotional state, maintaining a relationship with difficulty sleeping. In contrast, the positive answers in relation to adaptation to social distance, are perceived in patients with DM who maintained work activities at home. Conclusion: The psycho-emotional alterations have the potential to aggravate pathologies or properly be risk factors for chronic conditions, such as DM. The study demonstrates the importance of creating and protecting measures to reduce the effects of social distance on the lives of people at risk groups.